The Economic-legal Construction of Marriage and Divorce - Frańczuk, Magdalena (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
This paper focuses on the effects of both economic and legal aspects of marriage and divorce. I seek to verify the thesis that a marriage is a kind of legal and economic entity, similar in construction to a company regulated by civil law. To test the thesis, I examine the economic and legal implications of ending a marriage by divorce. The institution of marriage is likened to the civil law regulations of companies while also possessing a number of economic aspects.